The Effect of Physical Work Environment and Job Stress on Employee Job Satisfaction: A Case Study of UPTD Rusunawa Melong, Cimahi City - Leli Karisma Isabela Agustinawati; Dian Lestari (LP2M IAIN Palopo, 2026)
UPTD Rusunawa Melong in Cimahi City is currently facing challenges related to declining employee job satisfaction, as reflected in the increasing rate of employee turnover, transfer requests, and unexcused absenteeism. These conditions are presumed to be associated with inadequate physical working conditions together with the degree of occupational pressure faced by staff members in carrying out their responsibilities. This issue is important to investigate because employee fulfillment is essential for improving institutional performance and public service standards. This research investigates how workplace conditions and occupational pressure affect employee fulfillment at UPTD Rusunawa Melong in Cimahi City, both individually and simultaneously. This study adopted a quantitative research design. Information was obtained through questionnaires completed by 34 administrative staff members and processed using multiple regression analysis. The findings indicate that the physical work environment influences employee job satisfaction. In addition, job stress also affects employee job satisfaction. Collectively, the physical workplace conditions and occupational pressure influence employee satisfaction. These findings suggest that a conducive workplace conditions together with efficient job stress management are complementary factors in improving employee job satisfaction. This study concludes that creating a comfortable, safe, and supportive working environment, accompanied by effective job stress management, contributes to improving employee job satisfaction, which in turn supports better organizational performance.